2016
DOI: 10.1038/srep35800
|View full text |Cite
|
Sign up to set email alerts
|

Male food defence as a by-product of intersexual cooperation in a non-human primate

Abstract: Males in a number of group-living species fight in intergroup conflicts to defend access to food resources, a seemingly paradoxical behaviour, given that this resource does not usually limit male fitness directly. We investigated the mechanism(s) driving apparent male food defence in wild vervet monkeys (Chlorocebus aethiops pygerythrus) by testing the effect that female resource access, and female audience size and activity had on the response of focal males during simulated intergroup encounters. Males do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Because male and female vervet monkeys experience very different costs and benefits from participating in intergroup fights [14,44,67], they probably disagree on when to fight versus when to avoid engaging in intergroup aggression. This rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because male and female vervet monkeys experience very different costs and benefits from participating in intergroup fights [14,44,67], they probably disagree on when to fight versus when to avoid engaging in intergroup aggression. This rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 99%
“…However, we currently understand little of the strategies that other group-living animals use to resolve the conflicts of interest that arise during n-player cooperative activities. In vervet monkeys, the observed intra-and inter-individual variability in participation indicates that males and females experience very different costs and benefits from participating in intergroup fights [14,44,67]. These differences probably create selective pressure for the evolution of manipulative tactics.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings were made with a Marantz PMD661 (sampling rate of 44.1 kHz, resolution 24 bits) and a Sennheiser MKH416 microphone and stored as wav files. Recordings were based on ad libitum sampling, that is, any call observed during natural conflicts or during conflicts following food provisioning experiments carried out as part of other research, using four different experimental methods (‘box’ experiment: subjects had to retrieve food from a closed container [38], ‘jingle’ experiment: conditioned subjects were rewarded following individualised acoustic cues [39], ‘corn’ experiment: large plastic containers with corn were provided for the entire group to feed on [40, 41], ‘vervetable’ experiment: subjects had to copy a demonstrator’s object manipulations to access a small amount of food [42]). Conflicts occurred in all four experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A field experiment which simulated between-group encounters via playbacks found that males participated in encounters more often when a female monkey was visibly leading the agonistic encounter. The males' probability of participation did not vary with females' access to food resources, thus suggesting they were not participating to protect females' food sources, but in order to heighten their reputation as a cooperative group member (Arseneau-Robar, Müller, Taucher, van Schaik, & Willems, 2016b).…”
Section: Between-group Encountersmentioning
confidence: 95%